Pengaruh Teknologi Mobile Augmented Reality terhadap Niat Beli Looké Beauty - Yuliana Rahail; Jeanne Ellyawati (Departemen Ilmu Komunikasi FISIP Universitas Atma Jaya Yogyakarta, 2024)
The Mobile Augmented Reality (MAR) application is a marketing innovation that enhances consumer experiences by enabling virtual product trials despite distance and time constraints. This study examines the impact of MAR on purchase intention through perceived enjoyment and usefulness. Data were collected via online questionnaires using purposive and snowball sampling methods and analyzed using SmartPLS. Results indicate that virtual presence and devices influence enjoyment and usefulness directly and indirectly in shaping purchase intentions. Moreover, enjoyment and usefulness are found to have a positive effect on purchase intentions.